Porównanie Zygmunta III z Władysławem II Jagiełłą = The comparison of Sigismund III to Władysław II Jagiełło - Szpaczyński, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The comparison of Sigismund III to Władysław II Jagiełło, far too more reaching that this one which 150 years ago was superficially done by Antoni Morzycki and which barely signalised infair historian judgement, may definitely help to understand both policy and aspirations by the great monarch and help to denounce the suffering in historiography stereotypes and prejudices concerning his figure and his reign. In Poland both Sigismund III and Władysław II Jagiełło ruled almost half a century, in almost 200 years interval. The Polish-Swedish Union like the Polish-Lithuanian Union took place 2 centuries earlier opened new perspectives. Its main reasons, from the point of view of Sigismund were identical with Jagiełło's expectations.
Keywords: Zygmunt III Waza (król polski; 1566-1632); Władysław II Jagiełło (król polski; ok. 1352 lub 1362-1434); historiografia - Polska